PENGETAHUAN DAN SIKAP SISWA KELAS 7 TENTANG PEMANTAUAN JENTIK PASCA PELATIHAN DI SMP NEGERI 2 PRIGEN - Nur Aini; Dwiharini Puspitaningsih; Anndy Prastya (MEDICA MAJAPAHIT, 2023)
Improving the knowledge and attitudes of 7th grade junior high school students can be done by providing training on the courage to monitor larvae.This study aims to find out the impact of an online larva monitoring training on the knowledge and attitude of seventh graders at junior high school is 2 Prigen. In this study using a pre-experimental design in the form of one group pretest and posttest. This study was conducted in June 2021 with a population of 180 junior high school grade 7 students and was taken with the Proportional Random Sampling technique as many as 45 samples. Instruments were used in the form of multiple-choice and rating scales. The statistical test used is the Wilcoxon Test. The results showed that there was an increase in average knowledge and attitude scores, with the average before online Larva monitoring training being 8.20 and 27.38. Meanwhile, the average after online larva monitoring training was 11.22 and 31.44. By Wilcoxon test, there were significant results with the same p-value of 0.000 less than the significant value of 0.05. Based on these results, it can be concluded that there is an influence of online larva monitoring training on the knowledge and attitude of grade 7 students at SMP Negeri 2 Prigen. Puskesmas Bulukandang can provide training on larva monitoring online as an alternative program so that mosquito nest eradication can still be carried out as a prevention activity of DHF events originating from the school environment